Is a Specialist Employment Court a Better Forum for women? - Gay, M; Burton, B; Dalziel, L (Victoria University of Wellington Law Review, 1997)
A series of seminars on "Women and Employment" were held at Victoria University of Wellington in July 1997. The topic of the seminar was whether a specialist employment court is a better forum for women. The following article is based on Maxine Gay’s speech at the seminar. She believes that although the Employment Court may have made gender biased decisions, the Court should nevertheless be retained. She argues that a specialist employment court is important for women because it recognises that the employment contract is one in which the parties have unequal power and it should therefore be treated differently from other contracts. She takes the view that the suggestion by the Business Round Table and Employers’ Federation to abolish the Employment Court is part of a wider agenda to casualise the labour force and reduce the rights of employees.